Tinjauan Yuridis Terhadap Hak Asuh Anak Akibat Perceraian (Studi putusan Nomor 1034/Pdt.g/2022/Pa.Amb) - Devi Nur Sita Sari; Indra Yuliawan (Universitas Ngudi Waluyo, 2023)
One of the obligations of parents after marriage is to maintain, protect, educate and care for children until adulthood. The determination of the person who takes care of the child after the divorce is largely determined by the judge's decision. Sometimes child custody is given to the mother and sometimes child custody is given to the father. This study aims to determine the scope of custody of underage children (not yet mumayyiz) and custody of children who are already mumayyiz based on laws and regulations as well as judges' obstacles in making decisions regarding post-divorce child custody. This study uses primary legal material in the form of Law Number 16 of 2019 Amendment to Law Number 1 of 1974 concerning Marriage, secondary legal material in the form of judge's decisions and tertiary legal material in the form of legal dictionaries and encyclopedias. Data presentation was carried out descriptively and the data analysis method was qualitative, namely with a case study approach at the Ambarawa Religious Court, where this research could obtain the truth of a problem. The results of the study show that the appointment of a mother or father as a caregiver does not conflict with applicable laws and regulations as long as it guarantees the best interests of the child and both the mother and father have the right to care for the child even though the mother is more entitled to care for it. It is suggested to the judges that in deciding on a babysitter not only pay attention to the sex of the parents, but must guarantee the best interests of the child. It is suggested to policy makers to use this study as a reference in formulating new policies and to parents not to fight over child custody if they are unable to care for them properly. Abstrak Salah satu kewajiban orangtua pasca terjadinya perkawinan adalah memelihara, melindungi, mendidik dan mengasuh anak hingga dewasa. Penentuan orang yang mengasuh anak pasca perceraian sangat ditentukan oleh putusan hakim. Adakalanya hak asuh anak diberikan kepada ibu dan ada pula hak asuh anak diberikan kepada ayah. Penelitian ini bertujuan untuk mengetahui ruang lingkup hak asuh anak dibawah umur (belum mumayyiz) dan hak asuh anak yang sudah mumayyiz berdasarkan peraturan perundang-undangan serta hambatan hakim dalam memberikan putusan tentang hak asuh anak pasca perceraian. Penelitian ini menggunakan bahan hukum primer berupa Undang-Undang Nomor 16 Tahun 2019 Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, bahan hukum sekunder berupa putusan hakim dan bahan hukum tersier berupa kamus dan eksiklopedia hukum. Penyajian data dilakukan secara deskriptif dan metode analisis data secara kualitatif yaitu dengan pendekatan studi kasus di Pengadilan Agama Ambarawa, dimana dengan penelitian ini dapat memperoleh kebenaran dari suatu permasalahan. Hasil penelitian menunjukkan bahwa Penetapan ibu atau ayah sebagai pengasuh anak tidak bertentangan dengan peraturan perundangundangan yang berlaku selama menjamin kepentingan terbaik bagi anak dan baik ibu maupun ayah memiliki hak untuk mengasuh anak meskipun ibu orang yang lebih berhak mengasuhnya. Disarankan kepada hakim agar dalam memutuskan pengasuh anak tidak hanya memperhatikan jenis kelamin orangtua, akan tetapi harus menjamin kepentingan terbaik bagi anak. Disarankan kepada pengambil kebijakan agar menjadi kajian ini sebagai referensi dalam merumuskan kebijakan baru dan disarankan kepada orangtua agar tidak memperebutkan hak asuh anak jikalau tidak mampu mengasuhnya dengan baik.